Advances in the functional study of the Arabidopsis DNA Glycosylase MBD4L - Torres, José Roberto (2017)
DNA glycosylases play important roles in the life of all organisms, acting at initial stages of the base excision DNA repair system that excises and replaces damaged bases from DNA. Interestingly, some particular DNA glycosylases remove 5-methylcytosine (5-mC), whose replacement by cytosine (C) can produce DNA demethylation. In Arabidopsis, DNA glycosylases from the DEMETER family have such capacity, and act over some well characterized targets. Here, we studied a novel DNA glycosylase recently described named MBD4L (methyl-binding domain protein 4 like), that is homologous to the human DNA glycosylase MBD4. Curiously, MBD4L does not recognize 5-mC in vitro. Even so, we evaluated if MBD4L can affect DNA methylation of some particular genomic regions. For that, we selected genomic targets with different chromatin states (euchromatic- heterochromatic) and used CHOP-PCR assays to determine their methylation level. Studies were conducted in wildtype, mbd4l mutant and MBD4L over-expressing plants, under both basal and stress conditions. We found that MBD4L controls DNAmethylation at loci having different chromatin states. Moreover, the enzyme affects DNA methylation both at basal and stress condition. These results suggest that the action of MBD4L is not restricted to a particular chromatin state and probably contributes to stress-induced responses. The putative effects of MBD4L on the different genomic sites and on transcriptional regulation will be discussed.